THE DAY-NIGHT (CIRCADIAN) PHYSIOLOGICAL RHYTHMS OF LARGE ARCTIC CARNIVORS IN NATURAL CONTINUOUS LIGHT (SUMMER) AND CONTINUOUS DARKNESS (WINTER). - Folk,G. E.; Folk,M. A.; Brewer,M. C. (1966)
For two years observations on grizzly and black bears were obtained with Iowa physiological radio-capsules (EKG and body temperature, long life, short range, implantable). The condition of deep winter lethargy, which was demonstrated the first winter, was confirmed the second winter; summer sleeping heart rates (40 - 50 b/m) were replaced by the winter resting heart rates of lethargy (8 - 12 b/m) (Folk, Simmonds, Folk 1966). During this lethargy, after one to two months of remaining in one position in the den, bears have been known to become immediately active when stimulated. The study attempted to determine whether this capability depends on the time of day and whether the summer daily activity pattern is extinguished by the condition of lethargy. Recordings from two black and two grizzly bears provide the following: in lethargy (which lasted weeks) the amplitude and baseline of the daily activity pattern is much lower and the duration of the daily 'alert' period is narrowed. During the resting phase of the daily pattern in lethargy, the bears did not raise their heads when a standardized light stimulus was used. During lethargy a free-running rhythm with a period of about 23 hours and 52 minutes began. The activity pattern, which was changed in frequency slightly during lethargy, was typified by a 70% to 100% chance of finding the bears active near noon, and a 0% to 15% chance of finding them active near midnight, depending upon the extent of time already spend in lethargy. (Author) Pub. in Supplement A to Program presented at International Biometerological Congress (4th), Rutgers University, New Brunswick, N. J., September 1966.